Kinetochore-microtubule interactions "in check" by Bub1, Bub3 and BubR1: the dual task of attaching and signalling - Logarinho, Elsa (2008)
The spindle assembly checkpoint (SAC) prevents anaphase onset until all chromosomes accomplish proper bipolar attachments to the mitotic spindle and come under tension, thereby ensuring the fidelity of chromosome segregation. Despite significant advances in our understanding of SAC signalling, a clear link between checkpoint signalling and the molecular mechanisms underlying chromosome attachment to microtubules has not been established so far. However, independent studies from many groups have interestingly found that the bone-a-fide Bub1, BubR1 and Bub3 SAC proteins are themselves required for proper kinetochoremicrotubule (K-MT) interactions. Here, we review these findings and discuss the specific contribution of each of these proteins in the regulation of K-MT attachment, taking into consideration their interdependencies for kinetochore localization as well as their relationship with other proteins with a known role in chromosome attachment and congression.